Cover Image, Volume 11, Issue 11. (26th November 2017) - Chaturvedi, Vishal; Naskar, Deboki; Kinnear, Beverley F.; Grenik, Elizabeth; Dye, Danielle E.; Grounds, Miranda D.; Kundu, Subhas C.; Coombe, Deirdre R.
Abstract : The cover image, by Vishal Chaturvedi et al., is based on the Research Article Silk fibroin scaffolds with muscle‐like elasticity support in vitro differentiation of human skeletal muscle cells, DOI:10.1002/term.2227 .